Implementation of Activities of Police Management - Talijan, Momčilo; Ristović, Svetlana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
This paper presents the results of an empirical study on the implementation of activities of police management in the Republic of Serbia. The results will be exhibited at the following units: (1) to the current leaders in the police of the Republic of Serbia understand and rank their managerial roles and activities, and whether they see all their significance, especially for the effective and lawful execution of police duties; (2) if police executives recognize the influential factors of their management skills (effectiveness); (3) is there a need to be in the education system of the Ministry of Internal Affairs of the Republic of Serbia, that is, forms of education and training, implementing teaching programs for acquiring knowledge in the area of police management; (4) of the existence of a legal basis for the exercise of police management processes, and the extent to which they affect the efficient and lawful exercise of its functions (tasks) and (5) on the opinions and suggestions of the respondents in the exercise of roles and activities of police management.